Exploratory Study to Measure Awareness of Cybercrime in Saudi Arabia - et. al., Nourah Almrezeq, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Saudi Arabia is one of the fastest-growing nations in respect to using technology and the Internet. In recent years, the usage of these innovations has grown significantly. There’s a relationship between increasing Internet usage and rising cybercrimes. Although the spread of various protection techniques with different levels of security, there is a lack of application and public awareness. Protection techniques alone are not sufficient to confront cybercrimes, so awareness of cybersecurity is considered one of the most important reasons for reducing cybercrimes. Saudi Arabia is strengthening its interest in the field of cybersecurity. However, there is still an urgent need for research and investigation in awareness of cybersecurity and cybercrime. This study has been applied to students of Jouf University. The study has targeted a group of students who are not fully aware of digital crimes related to technology and the Internet. The study has shown a significant increase in awareness of cybersecurity. However, there is still a group of students with little or absence of awareness of understanding of cybersecurity. The survey analysis results have shown that for most of the participants who encountered cybercrimes, the respondents didn’t inform about the incidents to the local authorities and law enforcement. The majority of the participants emphasized the importance of enriching the digital content for the public with information about cybercrimes and how to deal with it according to local legislation. Literature review and survey results analysis show that there is a need for a framework that may help in developing awareness among Saudi's residents about cybercrimes.